Evaluation of 5‐cis‐Substituted Prolinamines as Ligands in Enantioselective, Copper‐Catalyzed Henry Reactions. Issue 10 (9th May 2016) - Kaldun, Johannes; Prause, Felix; Scharnagel, Dagmar; Freitag, Frederik; Breuning, Matthias
Abstract: The development of a new catalytic system for enantioselective Henry reactions, which permits superb 99 % ee with a broad variety of aldehydes, is presented. In‐depth structure–selectivity investigations with 33 5‐ cis ‐substituted prolinamines, prepared from methyl Boc‐l ‐pyroglutamate, revealed that an aromatic or sterically demanding aliphatic substituent in 5‐ cis position is crucial for high levels of stereocontrol, while bulkier substituents at the nitrogen atoms diminish both, enantioselectivities and reaction rates. The scope of the prime catalyst was expanded to gram‐scale and diastereomeric Henry reactions (up to 84:16 dr, 99 % ee ). In the course of mechanistic studies, it was proven that the resulting β‐nitro alcohols are configurationally stable under the reaction conditions. In addition, competition experiments were used to determine the relative reaction rates of some of the prolinamine‐modified catalysts. Abstract : Push it to the limit : In‐depth structure–selectivity studies with a broad range of 5‐ cis ‐substituted prolinamines reveal a highly enantioselective diamine–copper catalyst for asymmetric Henry reactions. Its scope is extended to gram‐scale and diastereoselective Henry reactions. The excellent stereodifferentiation solely arises from the asymmetric C, C‐coupling step.